Anticipate Password Security with Burp Suite Using the Brute Force Attack Method - Ika Mei Lina; -, Gilang Ryan Fernandes (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Website is one of the information and communication media that requires internet to run. Password generation is still less aware of user security. This provokes cyber criminals to carry out attacks to retrieve user login passwords. One possible attack is a brute force attack by experimenting with all possible passwords. This research aims to discuss brute force attack techniques and how to prevent them so that users can be more careful in creating passwords and be more aware of the security of their passwords. This research shows that the brute force method can work perfectly if there is no Captcha on the web login, limiting logins that do not block accounts for a long time, and not using Two Factor Authentication.